2019
DOI: 10.1515/jbnst-2018-0083
|View full text |Cite
|
Sign up to set email alerts
|

Economic Policy Uncertainty in the Euro Area: Cross-Country Spillovers and Macroeconomic Impact

Abstract: This paper analyzes spillovers and the macroeconomic effects of economic policy uncertainty (EPU) in Europe over the last two decades. Drawing on the newspaper-based uncertainty indices by Baker et al. (2016, Measuring Economic Policy Uncertainty. Quarterly Journal of Economics 131 (4): 1593–1636), we first use the Diebold and Yilmaz (2014 On the Network Topology of Variance Decompositions: Measuring the Connectedness of Financial Firms. Journal of Econometrics 182 (1): 119–134) connectedness index methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Binge and Boshoff (2020) also found that uncertainty impacts negatively on real GDP growth in South Africa. Contrary to these studies, Dey (2017) established significant positive effect of uncertainty on the real economy in India, while Volker et al. (2019) found that in Europe, policy uncertainty impacts heterogeneously across the countries.…”
Section: Literature Reviewmentioning
confidence: 58%
See 1 more Smart Citation
“…Binge and Boshoff (2020) also found that uncertainty impacts negatively on real GDP growth in South Africa. Contrary to these studies, Dey (2017) established significant positive effect of uncertainty on the real economy in India, while Volker et al. (2019) found that in Europe, policy uncertainty impacts heterogeneously across the countries.…”
Section: Literature Reviewmentioning
confidence: 58%
“…Binge and Boshoff (2020) also found that uncertainty impacts negatively on real GDP growth in South Africa. Contrary to these studies, Dey (2017) established significant positive effect of uncertainty on the real economy in India, while Volker et al (2019) found that in Europe, policy uncertainty impacts heterogeneously across the countries. Istiak and Serletis (2018) studied the G7 economies and found that the responses of real output to changes in economic policy uncertainty shocks are country-specific.…”
Section: Related Empirical Literaturementioning
confidence: 92%
“…The southern countries -Greece, Portugal, Spain and Italydid not become more resistant to economic shocks and did not move to a hopeful growth trajectory. During the crisis years, the euro caused the biggest damage in the weakest eurozone countries and widened the income disparities among member countries (Clausen, Schlösser, Thiem 2019).…”
Section: Chart 4 Economic Trends In the Usa And Europe During The Gre...mentioning
confidence: 99%